FOURIER TRANSFORM INFRARED SPECTROSCOPY INTERPRETATION DAN THERMOGRAVIMETRY/DIFFERENTIAL SCANNING CALORIMETRY ANALYSIS ON THERMOSETTING RESIN PRODUCTS WITH QUENCHING TREATMENT - Sukanto, Heru; Widodo, Purwadi Joko; Arifin, Zainal; Triyono, Joko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The quenching phenomenon observed in thermosetting epoxy resins necessitates a comprehensive investigation to mitigate its potential adverse effects on material performance. This study presents a novel approach to analyzing epoxy resins by employing Fourier Transform Infrared (FTIR) spectroscopy, Thermogravimetric Analysis (TGA), and Differential Scanning Calorimetry (DSC). Epoxy resin specimens were fabricated using a 1:1 weight ratio of diglycidyl ether bisphenol A resin and cycloaliphatic amine hardener. The quenching process was executed by submerging the specimens in water at ambient temperature following thermal exposure at 75, 100, 125, and 150°C. The FTIR and TGA/DSC analyses were verified by tensile testing, which revealed that FTIR analysis provided insights into the degree of crosslinking and hydroxyl index, while TGA/DSC data elucidated the glass transition temperature and crosslinking enthalpy. The findings demonstrated a direct correlation between the tensile strength and strain of the epoxy resin with changes in crosslinking enthalpy, and an inverse relationship with the hydroxyl index.